A low frequency rotational energy harvesting system - Febbo, Mariano (2016)
This paper presents a rotary power scavenging unit comprised of two systems of flexible beams connected by two masses which are joined by means of a spring, considering a PZT (QP16N, Midé Corporation) piezoelectric sheet mounted on one of the beams. The energy harvesting (EH) system is mounted rigidly on a rotating hub. The gravitational force on the mass es causes sustained oscillatory motion in the flexible beams as long as there is rotary motion. The intention is to use the EH system in the wireless autonomous monitoring of wind turbines under different wind condition s. Specifically , the development is oriented to monitor the dynamic state of the blades of a wind generator of 30 KW which rotates between 50 and 150 rpm. The paper shows a complete set of experimental results on three devices, modifying the amount of beams in the frame supporting the system . The results show an acceptable sustained voltage generatio n for the expected range, in the three proposed cases. Therefore, it is possible to use this system for generating energy in a low -frequency rotating environment. As an alternative, the system can be easily adapted to include an array of piezoelectr ic sheets to each of the beams , to provide more power generation.